Frequency of Primigravida with Eclampsia - Nimra Naeem, Sadia Habib, Asia Asghar, Neha Farooq, Sundus Nawaz, Sara Nasir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of primigravidas with eclampsia. Study Design: Cross-sectional study. Study Setting and Duration: Department of Obstetrics & Gynecology "C Ward", Ayub Medical Teaching Hospital, Abbottabad from 15th September 2020 to 15th March 2021. Methodology: One hundred and sixty women with eclampsia were included in the study. Demographic details as well as parity information and weight and primigravida were noted. Results: The mean age of 26.430±2.41 years, mean gestational age 34.539±2.40 weeks and mean weight was 65.727±4.47 Kg. Primigravida patients with eclampsia were 70.3%. Conclusion: Primigravida is one of the major factors in development of eclampsia. Keywords: Pregnancy, Eclampsia, Primigravida